PROSPECTS FOR USING HYDROGEN AS A RENEWABLE - Воловик, Д.М.; Кошлай, А.І.; Матвеева, Татьяна; Єрохіна, К.В. (Modern engineering and innovative technologies, 2024)
Abstract. This article discusses the potential of hydrogen as a renewable energy source. Here, the importance of the development of hydrogen energy in the context of energy, environmental and climate problems of today is shown. The history of hydrogen, it